Predictive Analysis of Factors Influencing Depression Status of Nurses in the COVID-19 Pandemic Intensive Care Unit - Li, Jing; Zhang, Yanhua; Li, Li; Yi, Wei; Hao, Yiwei; Bi, Yongjuan (Frontiers in Psychiatry, 2021)
Purpose: To understand the impact of COVID-19 on depression status of intensive care unit (ICU) nurses and analysis of predictive factors. Methods: The self-rating depression scale for ICU nurses of Beijing Ditan Hospital affiliated to Capital Medical University in March 2020 was employed to rate and analyze the results. Results: One-way analysis of variance compared the depression status of ICU nurses in different groups with respect to gender, education, health status, sleep status, COVID-19 infection prevention and control emergency training, first-line working hours, confidence to complete tasks, and stress perception assessment. The difference was statistically significant (P<0.05). The total score of stress perception, critical illness work experience, and academic qualifications are critical factors influencing depression. Conclusion: Medical institutions can make targeted psychological interventions based on factors, such as total pressure perception scores, critical illness work experience, and academic qualifications.